2018
DOI: 10.3847/1538-4357/aa978a
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical Effects in the Scattering Polarization Wings of the Ca i 4227 Å Resonance Line

Abstract: The linear polarization pattern produced by scattering processes in the Ca i 4227Å resonance line is a valuable observable for probing the solar atmosphere. Via the Hanle effect, the very significant Q/I and U/I line-center signals are sensitive to the presence of magnetic fields in the lower chromosphere with strengths between 5 and 125 G, approximately. On the other hand, partial frequency redistribution (PRD) produces sizable signals in the wings of the Q/I profile, which have always been thought to be inse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(119 citation statements)
references
References 26 publications
7
112
0
Order By: Relevance
“…Magnetic fields: The magnetic field can affect the Mg II energy levels through Zeeman effect. Previous studies have shown that the Mg II h&k lines are sensitive to Zeeman effect even for weak fields (e.g., Alsina Ballester et al 2016). By manually introducing a magnetic field with a strength up to 1000 Gauss in the RH code, we find that the Mg II Zeeman broadening in the Stokes I profiles is negligible.…”
Section: Discussionmentioning
confidence: 59%
“…Magnetic fields: The magnetic field can affect the Mg II energy levels through Zeeman effect. Previous studies have shown that the Mg II h&k lines are sensitive to Zeeman effect even for weak fields (e.g., Alsina Ballester et al 2016). By manually introducing a magnetic field with a strength up to 1000 Gauss in the RH code, we find that the Mg II Zeeman broadening in the Stokes I profiles is negligible.…”
Section: Discussionmentioning
confidence: 59%
“…At spectral distances from the line center that are much greater than both the Doppler width of the line and the magnetic splitting of the energy levels, the line emissivity is insensitive to both the Hanle and Zeeman effects, provided that the collisional broadening is significantly smaller than the natural width of the line (see LL04; also Appendix B of Alsina Ballester et al 2018). For illustrative purposes, throughout this work we will focus on a wing wavelength around which the linear polarization maximizes.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…In turn, such large U/I wing signals allow the ρ V U term to introduce a magnetic sensitivity in the Q/I wing signals. This mechanism causes both a rotation of the plane of linear polarization as the radiation travels through the solar atmosphere (see Alsina Ballester et al 2017) and an effective decrease of the degree of total linear polarization (see Alsina Ballester et al 2018). Recent RT investigations have indicated that such MO effects should play an important role in the wings of many strong chromospheric lines, such as the Mg ii k line (Alsina Ballester et al 2016), the Mg ii h & k lines (del Pino Alemán et al 2016), the Sr ii 407.8 nm line (Alsina Ballester et al 2017), and the Ca i 422.7 nm line (Alsina Ballester et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Alsina Ballester, Belluzzi, & Trujillo Bueno (2016) and del Pino Alemán, Casini, & Manso Sainz (2016; see also Manso Sainz, del Pino Alemán, & Casini 2017) have shown how PRD effects can combine with magneto-optical effects in an optically thick plasma to give rise to a significant Q U "rotation" of the scattering polarization in the near and far wings of deep resonance lines, even for magnetic strengths as small as a few gauss. Similar effects can be expected to manifest also for the model atom discussed in this paper.…”
Section: Scattering Polarization Of the Fe II Uv Multipletsmentioning
confidence: 99%
“…The results of this experiment confirmed important predictions from theoretical modeling of the Hanle effect in this line, but also opened new questions about the structure and magnetic topology of the upper solar chromosphere (Kano et al 2017). Motivated by the CLASP success, and by ongoing efforts in the modeling of the Mg II h-k doublet in the solar transition region spectrum at 280 nm (Belluzzi & Trujillo Bueno 2012;Alsina Ballester, Belluzzi, & Trujillo Bueno 2016;del Pino Alemán, Casini, & Manso Sainz 2016), the CLASP-2 mission (Narukage et al 2016) was proposed in order to measure the polarization produced by the joint action of scattering processes and the Hanle and Zeeman effects in these lines.…”
Section: Introductionmentioning
confidence: 99%